Mr. and Mrs. Bunny-- detectives extraordinaire! - Horvath, Polly. (Schwartz & Wade Books, 2012)
Middle-schooler Madeline's hippy parents have been kidnapped from Hornby Island, Canada, by foxes and Madeline, upon discovering that she can understand animal languages, hires two rabbit detectives to find them.